A Review on 3D Zinc Anodes for Zinc Ion Batteries. Issue 9 (19th July 2022) - Guo, Na; Huo, Wenjie; Dong, Xiaoyu; Sun, Zhefei; Lu, Yutao; Wu, Xianwen; Dai, Lei; Wang, Ling; Lin, Haichen; Liu, Haodong; Liang, Hanfeng; He, Zhangxing; et al.
Abstract: Zinc ion batteries (ZIBs) have been gradually developed in recent years due to their abundant resources, low cost, and environmental friendliness. Therefore, ZIBs have received a great deal of attention from researchers, which are considered as the next generation of portable energy storage systems. However, poor overall performance of ZIBs restricts their development, which is attributed to zinc dendrites and a series of side reactions. Constructing 3D zinc anodes has proven to be an effective way to significantly improve their electrochemical performance. In this review, the challenges of zinc anodes in ZIBs, including zinc dendrites, hydrogen evolution and corrosion, as well as passivation, are comprehensively summarized and the energy storage mechanisms of the zinc anodes and 3D zinc anodes are discussed. 3D zinc anodes with different structures including fiberous, porous, ridge‐like structures, plated zinc anodes on different substrates and other 3D zinc anodes, are subsequently discussed in detail. Finally, emerging opportunities and perspectives on the material design of 3D zinc anodes are highlighted and challenges that need to be solved in future practical applications are discussed, hopefully illuminating the way forward for the development of ZIBs. Abstract : In this review, the challenges and energy storage mechanisms of zinc anodes are summarized. Importantly, 3D zinc anodes with different structures are generalized in detail, including fiber, porous, ridge‐like structure, plated zinc anodes on different substrates, and other 3D zinc anodes. Furthermore, some views for 3D zinc anodes are put forward on the solutions and the future development direction.